Rola uwarunkowań przyrodniczych w rozwoju gospodarki ściekowej na przykładzie terenów wiejskich województwa wielkopolskiego - Stępniewska, Małgorzata (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2007)
Planning and implementation of sewage management investments require the consideration of environmental aspects. This is because the structure of the environment is decisive for the ecological efficiency of technical solutions used in the sewage management. A detailed analysis of environmental factors should form the basis for the distribution of funds to communes. The objective of the research is to check a hypothesis about the relationship between condition of sewage management and natural environment susceptibility to the influence of sewage. The research concerned the rural areas of the voivodeship of Wielkopolska. Seven factors were selected for analysis. Two of them concern the condition of sewage management, three are linked with the natural conditions, and two characterize the economic situation. It has been shown that in practice natural conditions are not taken into account in improvement of the sewage management. Condition of sewage management is not determined by affluence of their residents, but through activity of local leaders in acquiring public funds.